2023
DOI: 10.1186/s40001-023-01142-2
|View full text |Cite
|
Sign up to set email alerts
|

Photodistributed Stevens–Johnson syndrome and toxic epidermal necrolysis: a systematic review and proposal for a new diagnostic classification

Abstract: Background Ultraviolet radiation (UVR) exposure is commonly reported as a risk factor for Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). However, minimal evaluation of photo-induced SJS/TEN has been conducted. Thus, this review identifies all cases of SJS/TEN that are linked to an acute exposure of UVR and outlines the unifying characteristics of these cases. Furthermore, the theoretical pathogenesis, differential diagnoses, and proposed diagnostic criteria are defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 127 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…We read with interest the article by McKinley, Allen, and Michels titled "Photodistributed Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis: A Systematic Review and Proposal for a New Diagnostic Classification". The authors reviewed a total of 13 SJS/TEN cases that reported preceding and temporally related ultraviolet radiation (UVR) exposure to support their hypothesis that UVR was responsible for the distinct distribution of epidermal necrosis in these cases [ 1 ]. We commend the authors for their thorough and detailed review that makes a valuable contribution to the SJS/TEN literature while stimulating a discussion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by McKinley, Allen, and Michels titled "Photodistributed Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis: A Systematic Review and Proposal for a New Diagnostic Classification". The authors reviewed a total of 13 SJS/TEN cases that reported preceding and temporally related ultraviolet radiation (UVR) exposure to support their hypothesis that UVR was responsible for the distinct distribution of epidermal necrosis in these cases [ 1 ]. We commend the authors for their thorough and detailed review that makes a valuable contribution to the SJS/TEN literature while stimulating a discussion.…”
mentioning
confidence: 99%
“…McKinley et al specifically addressed this by excluding cases with a sharp cutoff typical of phototoxic reactions. However, they described SJS/TEN lesions beyond sun-exposed areas at first presentation, including mucosal and palmoplantar involvement in 12/12 and 5/6 cases, respectively [ 1 ]. Detailing the sequence in which the photoexposed and protected areas were initially affected would be helpful, otherwise this brings to question the veracity of attributing causality to UVR as an explanation for this clinical pattern.…”
mentioning
confidence: 99%